Effects of Sciatic Nerve Mobilization on Pain, Disability and Range in Patients with Lumbar Radicular Pain - Zainab, Sahreen Anwar, Ana Avaid, Wajeeha Fatimah, Wajida Perveen, Nimra Naseem (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Lumbar radicular pain is one of the leading causes of musculoskeletal disability. Variety of conventional treatment options are available. Aim: To find the effectiveness of sciatic nerve mobilization on disability and range of straight leg raise in patients with lumbar radicular pain. Study Design: Randomized control trail. Methodology: In this single blinded randomized control trial eighty patients were randomly divided in two groups. The experimental group received sciatic nerve mobilization along with routine physical therapy treatment whereas control group only received routine treatment in form of moist hot pack and back exercises. Outcomes were pain, disability and straight leg raise range measured through numeric pain rating scale, Modified Oswestry disability index MODI and inclinometer. The outcomes were assessed at baseline and at 4th and at 6th weeks of the treatment. Data was analyzed by SPSS software, version 20 as qualitative variables were expressed as mean ± SD. Paired sample t-test was applied. Results: Between groups analysis showed a significant difference in mean in both groups. Within group analysis was done using paired sample t test showed significant improvement (p <0.05) occurred in all variables in terms of pain, disability and straight leg raise range but sciatic nerve group had better improvement in terms of pain and disability as compared to conventional group. Conclusion: We concluded that sciatic nerve mobilization was an effective treatment for pain and disability in patients with lumbar radicular pain. Keywords: Lumbar Radicular Pain, Lumbar Radiculopathy, Sciatic Nerve Mobilization and Sciatic Nerve Neurodynamics.